Fifty percent of food restriction during gestation reduced the dendritic density of cerebrum and cerebellum of Rattus norvegicus newborn - Anwar Fauzi; Widjiati Widjiati; Hermanto T Joewono (Universitas Airlangga, 2018)
Objectives: To analyze the influence of 50 percent food restriction during pregnancy to the dendritic density of cerebellum and cerebellum of newborn Rattus norvegicus.Materials and Methods: Laboratory experimental study with single blind randomized post-test only control group design using animal model; pregnant Rattus norvegicus as treatment models. Subjects were divided into two groups: control group and treatment group which was exposed to 50% food restriction (FR 50%). At day 21, both group sacrificed and the cerebrum and cerebelum of the offsprings were prepared and stained with silver impregnation. We used parametric independent t-test in analyzing dendritic density.Results: In the cerebrum there was a significant difference in dendritic density between control (4.98+2.17) and treatment (2.69+0.76) groups with p=0.001 (p<0.05). In the cerebellum there was ALSO a significant difference in dendritic density between control (7.37+2.23) and treatment groups (3.01+0.64) with p=0.000 (p<0.05).Conclusions: The dendritic density of cerebrum and cerebellum of newborn Rattus norvegicusexposed to 50 percent of food restriction during pregnancy were lower than control.